A study on the level of public knowledge, attitudes and awareness towards public participation in solid waste management / Muhammad Syahmi Farhan Nasir - Nasir, Muhammad Syahmi Farhan (2018)
Environmental problems have become major issues especially for the Municipality that were responsible for waste management in their vicinity. The damaging effects of improper waste management has become apparent nowadays that it has given negative impacts towards our health. The level of knowledge and awareness among our community has diminished to the point that it affects public participation towards solid waste management. Furthermore, the public has shown negative attitudes and unfavourable behaviour towards the management of solid waste. Thus, this study aims to investigate the level of public knowledge, awareness and attitudes towards public participation in solid waste management, utilizing the empirical case study involving the residence living in Shah Alam, Selangor. Questionnaire has been used for the data collection that involves a total of 384 respondents who lives in Shah Alam, specifically in Section 6 and Section 25. The findings of this study revealed the level of public knowledge, attitude and awareness as well as their relationship towards public participation in solid waste management. The level for public knowledge and public awareness are low while the level for public attitudes is moderate. Besides, there is negative relationship between public attitude and public participation and the most influential factors towards public participation in regards of solid waste management is public knowledge.